2021
DOI: 10.11159/icsect21.lx.110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beam Design on Progressive Collapse Resistance of RC Framed Structures

Abstract: This study presents numerical findings of an investigation into the effect of beam dimensions and sagging and hogging reinforcement ratios on progressive collapse response of reinforce concrete (RC) frame sub-assemblages when faced with an interior column loss. Also the flexibility of the beams in terms of height to span ratio which is directly correlated with compressive arch action and catenary action mechanisms is not directly emphasized. To this aim, four RC frame sub-assemblages of constant span lengths a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The complete information on the fiber-element-based numerical model parameters and framework can be found in [53]. The authors have also used the fiber element-based software SeismoStruct in previous studies [40][41][42][43][44][45][46]49] on the simulation of the progressive collapse of RC structures.…”
Section: Numerical Modeling For Progressive Collapse Analysis Of Desi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The complete information on the fiber-element-based numerical model parameters and framework can be found in [53]. The authors have also used the fiber element-based software SeismoStruct in previous studies [40][41][42][43][44][45][46]49] on the simulation of the progressive collapse of RC structures.…”
Section: Numerical Modeling For Progressive Collapse Analysis Of Desi...mentioning
confidence: 99%
“…Substantial variances in the progressive collapse patterns were highlighted as the considered parametric changed. Elkholy et al [49] confirmed that the beam height had a tangible effect on the sub-assemblage resistance to progressive collapse and demonstrated that varying the concrete and steel quantities had a significant impact on the ductility and the cost of the frame structure.…”
Section: Introductionmentioning
confidence: 99%